Monitoring service delivery for universal health coverage: the Service Availability and Readiness Assessment - Kathryn O'Neill; Marina Takane; Ashley Sheffel; Carla Abou-Zahr; Ties Boerma (The World Health Organization, 2013)
Objective To describe the Service Availability and Readiness Assessment (SARA) and the results of its implementation in six countries across three continents. Methods The SARA is a comprehensive approach for assessing and monitoring health service availability and the readiness of facilities to deliver health-care interventions, with a standardized set of indicators that cover all main programmes. Standardized data-collection instruments are used to gather information on a defined set of selected tracer items from public and private health facilities through a facility sample survey or census. Results from assessments in six countries are shown. Findings The results highlight important gaps in service delivery that are obstacles to universal access to health services. Considerable variation was found within and across countries in the distribution of health facility infrastructure and workforce and in the types of services offered. Weaknesses in laboratory diagnostic capacities and gaps in essential medicines and commodities were common across all countries. Conclusion The SARA fills an important information gap in monitoring health system performance and universal health coverage by providing objective and regular information on all major health programmes that feeds into country planning cycles.